Low-Level Laser Therapy Stimulates Proliferation in Head and Neck Squamous Cell Carcinoma Cells - Bamps, Marieke; Dok, Rüveyda; Nuyts, Sandra (Frontiers in Oncology, 2018)
Objectives: Low-level laser therapy (LLLT) is a promising non-invasive treatment option for oropharyngeal mucositis, which is a common side effect of many oncological treatments. LLLT is known for its wound healing properties due to the stimulation of cellular processes, such as proliferation, migration and differentiation. Controversy exists on the possible stimulatory effect of LLLT on head and neck cancer (HNSCC) cells in patients treated with radiotherapy. The aim of this study was to evaluate the biostimulatory effect together with the underlying mechanisms of LLLT on HNSCC cancer cells and normal epithelial cells. Materials and methods: HNSCC cell lines (SCC154, SQD9 and SCC61) and human tonsil epithelial cells were exposed to a Gallium-Aluminium-Arsenide diode laser (830 nm, 150 mW) with energy densities of 0, 1 and 2 J/cm². The proliferation potential of the cells was assessed by Sulforhodamine B assay, immunoblotting (mitogenic pathways), immunocytochemistry (Ki67) and flow cytometry (PI cell cycle staining). Results: Cell proliferation was increased in HNSCC cell lines after laser irradiation with 1 J/cm², whereas no significant increase was seen after laser irradiation with 2 J/cm². In contrast, no effect on cell proliferation was seen in the human tonsil epithelial cells after laser irradiation with any of the energy densities. The increased proliferation was associated with elevated levels of pAKT, pERK and Ki67 protein expression and cell cycle progression. Conclusion: Our results show that LLLT increases cell proliferation in a dose-dependent manner in HNSCC cells but not in normal epithelial tonsil cells. These results suggest that LLLT has to be used with caution when treating oropharyngeal mucositis in HNSCC patients since tumor cells present in the LLLT irradiation field could be triggered by LLLT.